Relationship Analysis between Mass Customization and Rationalized Quality Costs - Khdier Salman Al-hamad; Rajaa Rasheed Abdul-Sattar (Journal of Madenat Alelem University College, 2022)
Mass customization is one of the new models that lead to quick response to customer requests and participation in product or service design processes that meet their needs. This study aims to reduce the cost of quality in the economic units through mass customization and finish the external and internal failure costs. The most important conclusion of the study is that the mass customization system of modern means will help the management of economic units to program their production according to the customer’s desire. The most crucial conclusion, that study reached is the need to adopt high-tech systems and then eliminate all costs of external and internal failure.